PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK SELEKSI PENERIMAAN CALON MAHASISWA BARU DI POLITEKNIK NEGERI SAMARINDA - Yusni Nyura; Anton Topadang (Politeknik Negeri Samarinda, 2016)
Selection of new student enrollment is a process, method, screening or selection of prospective students in the academic ability is the best candidate for learning sector in higher education institutions. Likewise, the selection is done through the search Interests and Abilities Polytechnic (PMDK-PN), that the selection of new student enrollment is done by tracking the academic ability of prospective students who are considered to have the potential and the quality seeds region. To screen potential new students need a fairly rigorous selection process, the goal is to screen prospective new students who qualified, so it has a high competitive graduates who can compete with the outside world. But the selection process for new students who walk for this is still done manually, where the data of prospective students sorted by highest value of the quotas each district in each department, so that it often takes a long time and requires a high accuracy. It is considered less effective and less efficient, since the ability / potential of prospective new students in each district is different. From the above problems, the researchers will design an application that can be used for the selection of new student enrollment using artificial neural network method. The method used in this study using a software system development Software Development Life Cycle (SDLC) that includes the needs analysis phase, prototyping, prototype evaluation, development and testing final software. Key word: Selection, Software Development Life Cycle (SDLC)